Evaluation of Innovation Efficiency of High-Tech Enterprise Knowledge Supply Chain Based on AHP-DEA - Huiyuan Han; Xiaomin Gu (Journal of Mathematics)
This paper introduces a qualitative analysis on the efficiency evaluation of the knowledge supply chain by combining the analytic hierarchy process (AHP) with data envelopment analysis (DEA), drawing on existing literature to determine the index weight through the scoring of industry experts, and selecting appropriate input and output indicators to construct a knowledge supply chain efficiency evaluation system. The system was then applied to the supply chain of a number of high-tech enterprises. The results identified innovation efficiency differences of the knowledge supply chain in these enterprises, along with best practices and suggestions for the current knowledge supply chain efficiency.